Connecting Health and Emergency Management: A Review of Disaster Response: Medical and Health Policies by Arnauld Nicogossian and Bonnie Stabile (Ed.). Issue 4 (December 2015) - Robinson, Scott E.
Abstract : The field of risk, hazards, and crises (if, indeed, it is coherent enough to be called a field) crosses over a staggering array of traditional and emergent academic disciplines. One point of intersection in particular seems to have generated less attention than it warrants—the intersection of disaster research and public health. It is in the context of the noticeable gap between public health work on disasters and work in emergency management that the recent edited volume by Nicogossian and Stabile emphatically stands out. The review will discuss each of the chapters in this volume and conclude with several crosscutting themes that emerge.